Preparation of fiber-reinforced low-density high-flame-retardant sheet molding compound

Through the preparation of fiber-reinforced low-density high-fire-retardant sheet-like molding materials, the synergistic effect of modified carbon nanotubes and DOPO is solved, and the problem of difficult flame retardant performance and density in the prior art is achieved, and efficient flame retardant effect is achieved and lightweight material properties.

CN119119701AInactive Publication Date: 2024-12-13FUSHIDE NEW MATERIALS MFG (HUAIAN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411143870.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While pursuing lightweight and high flame retardant properties, existing flame retardant sheet molding materials are difficult to meet the needs of modern industry for low density and excellent mechanical properties, especially in the automotive, construction and aviation fields, traditional high-density flammable materials. The requirements of the new energy industry can no longer be met.

Method used

The preparation method of fiber-reinforced low-density high-fire-retardant sheet-like molding material is adopted. By grafting and modifying carbon nanotubes and using them in conjunction with DOPO, the flame retardant properties and strength of the material are enhanced while reducing the overall density of the material. The specific steps include reacting N-benzyl-N-(3-butene)amine with methyl dichlorophosphate to form intermediate A, followed by 2,4-diamino-6-phenyl-1,3,5 -Triazine reacts with acidified carbon nanotubes to obtain modified carbon nanotubes, combined with vinyl resin and other components, and then mature after compression and impregnation through the SMC unit.

Benefits of technology

It effectively improves the flame retardant performance and strength of sheet-shaped film plastics, reduces material density, delays thermal decomposition, forms a stable carbon layer to isolate oxygen and heat, and significantly improves the flame retardant effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of plastic preparation, in particular to preparation of a fiber-reinforced low-density high-flame-retardant sheet molding compound. Comprising the following steps: 1, adding matrix resin and a low shrinkage agent into a stirring kettle, stirring, adding a release agent, a polymerization inhibitor, a cross-linking agent, an impregnating compound, PE powder, a flame retardant and an initiator, and stirring to obtain resin paste; 2, inputting the resin paste and a thickening agent into a mixing trough through a pump, then adding reinforced fibers through an SMC unit, and pressing and dipping through a pressure roller to obtain a sheet; and 3, rolling and packaging the sheet material, feeding the sheet material into a drying room, and curing to obtain the sheet molding compound. The preparation method has the beneficial effects that the carbon nanotubes are subjected to graft modification and cooperate with DOPO to play a role together, so that the flame retardant property and strength of the obtained sheet-shaped film plastic are effectively enhanced. And meanwhile, the porosity of the material can be increased by the carbon nanotubes, so that the overall density of the material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of plastic preparation, in particular to the preparation of a fiber-reinforced low-density high-flame-retardant sheet molding compound. Background Art

[0002] Low-density and high-flame-retardant sheet molding compound is a special reinforced plastic material that combines the characteristics of low density and high flame retardancy and is widely used in the fields of automobiles, construction, electrical and aviation. The development background of this material is closely related to the high requirements of modern society for material performance.

[0003] With the development of science and technology and the enhancement of environmental awareness, traditional high-density, flammable materials can no longer meet the needs of modern industry. Especially in the context of lightweighting and improving safety of automobiles, the demand for low-density, high-flame-retardant materials is growing. Automakers seek to use lighter materials to reduce fuel consumption and emissions while maintaining or improving vehicle safety. This requires that the materials must not only be light, but also have good mechanical properties and flame retardant properties to prevent fire risks. The construction industry also has strict requirements on the flame retardant properties of materials to ensure personnel safety and reduce losses caused by fire. The electrical industry also needs to use flame retardant materials to protect electronic equipment and cables from overheating and fire. The aviation field has more stringent requirements for materials, which must be lightweight to improve fuel efficiency and have excellent flame retardant properties to ensure flight safety.

[0004] At present, the application and demand of flame-retardant sheet molding compounds in the composite material industry are increasing. Considering the cost and ease of operation, most flame-retardant sheet molding compounds are added with aluminum hydroxide as a flame retardant. However, given that the density of aluminum hydroxide is relatively high, with the increasing requirements of the new energy industry, while requiring the material to be flame-retardant, it is also necessary to achieve lightweight, which has led to the development of low-density and high-flame-retardant materials. Therefore, the present invention prepares a fiber-reinforced low-density and high-flame-retardant sheet molding compound. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a fiber-reinforced low-density high-flame-retardant sheet molding compound to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] More optimally, the sheet molding compound includes the following components: by weight, 55-75 parts of base resin, 12-25 parts of low shrinkage agent, 1-3 parts of release agent, 0.2-0.4 parts of inhibitor, 0.5-1 parts of thickener, 20-35 parts of flame retardant, 1-3 parts of cross-linking agent, 0.4-1 parts of initiator, 0.2-0.5 parts of wetting agent, 0.5-1.5 parts of PE powder, and 10-25 parts of reinforcing fiber.

[0008] More optimally: the matrix resin includes one or more of unsaturated polyester and vinyl resin, and has good wettability to glass fiber.

[0009] More optimally: the low shrinkage agent includes one or more of a polystyrene low shrinkage agent and a saturated polyester low shrinkage agent, and has excellent low shrinkage rate and colorability;

[0010] The release agent includes one or more of zinc stearate, magnesium stearate, and calcium stearate, which can form an isolation layer between the sheet molding compound and the mold, making it easy to demold during molding;

[0011] The inhibitor includes one or more of hydroquinone, benzoquinone, trimethylbenzyl ammonium chloride and bromide, which can extend the storage time of the sheet molding compound;

[0012] The thickener includes one or more of calcium oxide, magnesium oxide, calcium hydroxide, and magnesium hydroxide; the cross-linking agent is styrene, which is mainly used to ripen the sheet material and increase the viscosity of the ripened material to achieve the effect of easy film tearing;

[0013] The initiator includes one or more of tert-butyl perbenzoate, benzoyl peroxide, tert-butyl peracetate, and tert-amyl perbenzoate; and the reinforcing fiber is alkali-free glass fiber.

[0014] More optimally: the flame retardant includes one or more of melamine, DOPO, and DMMP.

[0015] More optimally: the flame retardant also includes modified carbon nanotubes.

[0016] More optimally: the preparation process of the modified carbon nanotubes is:

[0017] S1: (1) dissolving N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution; (2) adding the N-benzyl-N-(3-butene)amine solution dropwise to methyl dichlorophosphate at 70-80° C., and adding triethylamine, reacting for 4-5 hours, filtering, washing, and drying to obtain intermediate A;

[0018] S2: (1) dissolving 2,4-diamino-6-phenyl-1,3,5-triazine and intermediate A in ethanol respectively to obtain a 2,4-diamino-6-phenyl-1,3,5-triazine solution and an intermediate A solution; (2) adding the intermediate A solution dropwise to the 2,4-diamino-6-phenyl-1,3,5-triazine solution at 60-70° C., adding diisopropylethylamine, and reacting for 6-8 hours to obtain intermediate B;

[0019] S3: Dissolve the intermediate B and the acidified carbon nanotubes in ether, add 1,3-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stir for 30-40 minutes, heat to 70-80° C., react for 4-5 hours, and obtain modified carbon nanotubes.

[0020] More optimally, the intermediate A comprises the following components: by weight, 10-12 parts of methyl dichlorophosphate, 12-14 parts of N-benzyl-N-(3-butene)amine, and 1-2 parts of triethylamine; the intermediate B comprises the following components: by weight, 10-12 parts of 2,4-diamino-6-phenyl-1,3,5-triazine, 8-10 parts of intermediate A, and 1-2 parts of diisopropylethylamine; the modified carbon nanotubes comprise the following components: by weight, 15-20 parts of intermediate B, 20-25 parts of acidified carbon nanotubes, 2-4 parts of 1,3-dicyclohexylcarbodiimide, and 2-4 parts of 4-dimethylaminopyridine.

[0021] More optimally: the flame retardant is a composition of modified carbon nanotubes and DOPO, and the weight ratio of the two is 1:

[0022] (1-2.5).

[0023] More optimally: the preparation of the fiber-reinforced low-density high-flame-retardant sheet molding compound comprises the following steps:

[0024] Step 1: Add the base resin and low shrinkage agent into a stirring kettle, stir at a speed of 800-1000r / min for 2-5min, then add the release agent, polymerization inhibitor, crosslinking agent, wetting agent, PE powder, flame retardant, initiator, stir at a speed of 1000-1200r / min for 5-8min to obtain a resin paste;

[0025] Step 2: The resin paste and thickener are pumped into the mixing tank, and then through the SMC unit, the reinforcing fiber is added, and the sheet is obtained by pressing and impregnating with a pressure roller;

[0026] Step 3: Roll up and package the sheet, send it to a drying room for curing, and obtain a sheet molding compound.

[0027] More optimally, the aging process parameters are: temperature 40-42°C, time 10-12h.

[0028] The present invention effectively enhances the flame retardancy and strength of the obtained sheet-like film plastic by grafting and modifying carbon nanotubes and cooperating with DOPO. At the same time, carbon nanotubes can increase the porosity of the material and reduce the overall density of the material. The details are as follows:

[0029] First, through chemical bonding, organic molecular chains are grafted onto the surface of carbon nanotubes, in which the structure of terminal olefins effectively enhances their compatibility with the matrix vinyl resin. At the same time, carbon nanotubes, as reinforcement materials, can enhance the physical properties of sheet film plastics.

[0030] Second: The molecular chains grafted with carbon nanotubes contain structures such as triazine and PN, which can maintain the integrity of the structure at high temperatures, thereby delaying the thermal decomposition of the material. In addition, when exposed to heat, it helps to form a stable carbon layer on the surface of the material, which can isolate oxygen and heat and slow down the combustion process inside the material. At the same time, DOPO can decompose at high temperatures, releasing substances such as phosphoric acid or polyphosphoric acid to form a protective layer, isolate oxygen and heat, and enhance the stability of the above carbon layer, further improving the flame retardant effect. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that the following parts are by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, carbon nanotubes CAS is 308068-56-6, purchased from Merck; γ-aminopropyltriethoxysilane CAS is 919-30-2, purchased from Aladdin; 1,3-dicyclohexylcarbodiimide (DCC) CAS is 538-75-0, the manufacturer is Anaiji; 4-dimethylaminopyridine (DMAP) CAS is 1122-58-3 , the manufacturer is Kaisai Chemical; N-benzyl-N-(3-butene)amine CAS is 17150-62-8, the manufacturer is Bailingwei; 2,4-diamino-6-phenyl-1,3,5-triazine CAS is 91-76-9, the manufacturer is Kunlun Biological; methyl dichlorophosphate CAS is 677-24-7, purchased from Merck; vinyl resin model is MFE-2; low shrinkage agent model is GPPS525; alkali-free glass fiber model is ER15-4800; sizing agent model is BYK-9010.

[0033] Pre-preparation: Place the carbon nanotubes in a 500 ml mixed acid solution of concentrated nitric acid and concentrated sulfuric acid, wherein the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 3:1. After ultrasonic treatment at room temperature for 4 hours, add distilled water to dilute the mixed solution, filter with a filter membrane, continue to add an appropriate amount of distilled water to dilute, let it stand, pour out the supernatant, filter with suction, repeat the above operation several times until the pH value of the supernatant is about 7, filter out the carbon nanotubes with the filter membrane, place it in an oven to dry, and grind it for 0.5 to 1 hour to obtain acidified carbon nanotubes.

[0034] Example 1: Preparation of a fiber-reinforced low-density high-flame-retardant sheet molding compound, comprising the following steps:

[0035] Preparation of modified carbon nanotubes:

[0036] S1: Dissolve 12 parts of N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution, heat to 70°C, dropwise add the N-benzyl-N-(3-butene)amine solution into 10 parts of methyl dichlorophosphate solution, control the amount of methyl dichlorophosphate to be excessive so that the amino group in the N-benzyl-N-(3-butene)amine reacts with only one of the phosphorus-chlorine bonds, add 1 part of an acid-binding agent, triethylamine, react for 4 hours, filter, wash, and dry to obtain an intermediate A;

[0037] S2: Dissolve 10 parts of 2,4-diamino-6-phenyl-1,3,5-triazine and 8 parts of intermediate A in ethanol respectively, raise the temperature to 60°C, add intermediate A dropwise to 2,4-diamino-6-phenyl-1,3,5-triazine, control the excess of 2,4-diamino-6-phenyl-1,3,5-triazine, add 1 part of acid-binding agent diisopropylethylamine, react for 6 hours, and obtain intermediate B;

[0038] S3: Dissolve 15 parts of intermediate B and 20 parts of acidified carbon nanotubes in ether, add 2 parts of 1,3-dicyclohexylcarbodiimide and 2 parts of 4-dimethylaminopyridine, stir for 30 minutes, heat to 70°C, react for 4 hours, and obtain modified carbon nanotubes.

[0039] Step 1: Add 60 parts of vinyl resin and 20 parts of polystyrene type low shrinkage agent into a stirring tank, stir at a speed of 800 r / min for 2 minutes, then add 2.5 parts of zinc stearate, 35 parts of flame retardant (10 parts of modified carbon nanotubes, 25 parts of DOPO), 1.5 parts of styrene, 0.5 parts of wetting agent, 1 part of PE powder, 0.4 parts of benzoquinone, 0.8 parts of tert-butyl peroxybenzoate, stir at a speed of 1000 r / min for 5 minutes to obtain a resin paste;

[0040] Step 2: The resin paste and 1 part of calcium hydroxide are pumped into the mixing tank, the mixing pump speed is turned on at 1250r / min, and then input into the scraper tank, through the SMC unit, 25 parts of alkali-free glass fiber are added, and the impregnation is pressed by a pressure roller, and the equipment running speed is controlled to 10m / min to obtain a sheet;

[0041] Step 3: Roll and pack the sheet, send it to a drying room, control the temperature of the drying room at 40°C, and cure it for 10 hours to obtain a sheet molding compound.

[0042] Example 2: Preparation of a fiber-reinforced low-density high-flame-retardant sheet molding compound, comprising the following steps:

[0043] Preparation of modified carbon nanotubes:

[0044] S1: Dissolve 14 parts of N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution, heat to 80°C, dropwise add the N-benzyl-N-(3-butene)amine solution to 12 parts of methyl dichlorophosphate, control the amount of methyl dichlorophosphate to be excessive so that the amino group in the N-benzyl-N-(3-butene)amine reacts with only one of the phosphorus-chlorine bonds, add 2 parts of an acid-binding agent, triethylamine, react for 4 hours, filter, wash, and dry to obtain an intermediate A;

[0045] S2: Dissolve 10 parts of 2,4-diamino-6-phenyl-1,3,5-triazine and 8 parts of intermediate A in ethanol respectively, raise the temperature to 60°C, add intermediate A dropwise to 2,4-diamino-6-phenyl-1,3,5-triazine, control the excess of 2,4-diamino-6-phenyl-1,3,5-triazine, add 2 parts of acid-binding agent diisopropylethylamine, react for 8 hours, and obtain intermediate B;

[0046] S3: Dissolve 20 parts of intermediate B and 25 parts of acidified carbon nanotubes in ether, add 4 parts of 1,3-dicyclohexylcarbodiimide and 4 parts of 4-dimethylaminopyridine, stir for 40 minutes, heat to 80°C, react for 5 hours, and obtain modified carbon nanotubes.

[0047] Step 1: Add 60 parts of vinyl resin and 20 parts of polystyrene type low shrinkage agent into a stirring tank, stir at a speed of 1000 r / min for 5 minutes, then add 2.5 parts of zinc stearate, 32 parts of flame retardant (10 parts of modified carbon nanotubes, 22 parts of DOPO), 1.5 parts of styrene, 0.5 parts of wetting agent, 1 part of PE powder, 0.4 parts of benzoquinone, 0.8 parts of tert-butyl peroxybenzoate, stir at a speed of 1200 r / min for 8 minutes to obtain a resin paste;

[0048] Step 2: The resin paste and 1 part of calcium hydroxide are pumped into the mixing tank, the mixing pump speed is turned on at 1250r / min, and then input into the scraper tank, through the SMC unit, 25 parts of alkali-free glass fiber are added, and the impregnation is pressed by a pressure roller, and the equipment running speed is controlled to 10m / min to obtain a sheet;

[0049] Step 3: Roll and pack the sheet, send it to the drying room, control the temperature of the drying room at 42°C, and cure it for 12 hours to obtain the sheet molding compound.

[0050] Example 3: Preparation of a fiber-reinforced low-density high-flame-retardant sheet molding compound, comprising the following steps:

[0051] Preparation of modified carbon nanotubes:

[0052] S1: Dissolve 13 parts of N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution, heat to 80°C, dropwise add the N-benzyl-N-(3-butene)amine solution into 11 parts of methyl dichlorophosphate, control the amount of methyl dichlorophosphate to be excessive so that the amino group in the N-benzyl-N-(3-butene)amine reacts with only one of the phosphorus-chlorine bonds, and add 1.5 parts of an acid-binding agent, triethylamine, react for 4 hours, filter, wash, and dry to obtain an intermediate A;

[0053] S2: Dissolve 11 parts of 2,4-diamino-6-phenyl-1,3,5-triazine and 9 parts of intermediate A in ethanol respectively, raise the temperature to 60°C, add intermediate A dropwise to 2,4-diamino-6-phenyl-1,3,5-triazine, control the excess of 2,4-diamino-6-phenyl-1,3,5-triazine, add 1.5 parts of acid-binding agent diisopropylethylamine, react for 8 hours, and obtain intermediate B;

[0054] S3: 18 parts of intermediate B and 22 parts of acidified carbon nanotubes were dissolved in ether, 3 parts of 1,3-dicyclohexylcarbodiimide and 3 parts of 4-dimethylaminopyridine were added, stirred for 40 minutes, heated to 80°C, reacted for 5 hours, and modified carbon nanotubes were obtained.

[0055] Step 1: Add 60 parts of vinyl resin and 20 parts of polystyrene type low shrinkage agent into a stirring tank, stir at a speed of 1000r / min for 5min, then add 2.5 parts of zinc stearate, 30 parts of flame retardant (10 parts of modified carbon nanotubes, 20 parts of DOPO), 1.5 parts of styrene, 0.5 parts of wetting agent, 1 part of PE powder, 0.4 parts of benzoquinone, 0.8 parts of tert-butyl peroxybenzoate, stir at a speed of 1200r / min for 8min to obtain a resin paste;

[0056] Step 2: The resin paste and 1 part of calcium hydroxide are pumped into the mixing tank, the mixing pump speed is turned on at 1250r / min, and then input into the scraper tank, through the SMC unit, 25 parts of alkali-free glass fiber are added, and the impregnation is pressed by a pressure roller, and the equipment running speed is controlled to 10m / min to obtain a sheet;

[0057] Step 3: Roll and pack the sheet, send it to a drying room, control the temperature of the drying room at 42°C, and cure it for 11 hours to obtain a sheet molding compound.

[0058] Example 4: Preparation of a fiber-reinforced low-density high-flame-retardant sheet molding compound, comprising the following steps:

[0059] Preparation of modified carbon nanotubes:

[0060] S1: Dissolve 12 parts of N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution, heat to 70°C, dropwise add the N-benzyl-N-(3-butene)amine solution into 10 parts of methyl dichlorophosphate solution, control the amount of methyl dichlorophosphate to be excessive so that the amino group in the N-benzyl-N-(3-butene)amine reacts with only one of the phosphorus-chlorine bonds, add 1 part of an acid-binding agent, triethylamine, react for 4 hours, filter, wash, and dry to obtain an intermediate A;

[0061] S2: Dissolve 10 parts of 2,4-diamino-6-phenyl-1,3,5-triazine and 8 parts of intermediate A in ethanol respectively, raise the temperature to 60°C, add intermediate A dropwise to 2,4-diamino-6-phenyl-1,3,5-triazine, control the excess of 2,4-diamino-6-phenyl-1,3,5-triazine, add 2 parts of acid-binding agent diisopropylethylamine, react for 8 hours, and obtain intermediate B;

[0062] S3: Dissolve 20 parts of intermediate B and 25 parts of acidified carbon nanotubes in ether, add 4 parts of 1,3-dicyclohexylcarbodiimide and 4 parts of 4-dimethylaminopyridine, stir for 40 minutes, heat to 80°C, react for 5 hours, and obtain modified carbon nanotubes.

[0063] Step 1: Add 60 parts of vinyl resin and 20 parts of polystyrene type low shrinkage agent into a stirring tank, stir at a speed of 1000r / min for 5min, then add 2.5 parts of zinc stearate, 28 parts of flame retardant (10 parts of modified carbon nanotubes, 18 parts of DOPO), 1.5 parts of styrene, 0.5 parts of wetting agent, 1 part of PE powder, 0.4 parts of benzoquinone, 0.8 parts of tert-butyl peroxybenzoate, stir at a speed of 1200r / min for 8min to obtain a resin paste;

[0064] Step 2: The resin paste and 1 part of calcium hydroxide are pumped into the mixing tank, the mixing pump speed is turned on at 1250r / min, and then input into the scraper tank, through the SMC unit, 25 parts of alkali-free glass fiber are added, and the impregnation is pressed by a pressure roller, and the equipment running speed is controlled to 10m / min to obtain a sheet;

[0065] Step 3: Roll and pack the sheet, send it to a drying room, control the temperature of the drying room at 42°C, and cure it for 11 hours to obtain a sheet molding compound.

[0066] Comparative Example 1: No modified carbon nanotubes were added, and the rest was the same as Example 4, specifically as follows:

[0067] Step 1: Add 60 parts of vinyl resin and 20 parts of polystyrene type low shrinkage agent into a stirring kettle, stir at a speed of 1000 r / min for 5 minutes, then add 2.5 parts of zinc stearate, 28 parts of flame retardant (28 parts of DOPO), 1.5 parts of styrene, 0.5 parts of wetting agent, 1 part of PE powder, 0.4 parts of benzoquinone, 0.8 parts of tert-butyl perbenzoate, stir at a speed of 1200 r / min for 8 minutes to obtain a resin paste;

[0068] Step 2: The resin paste and 1 part of calcium hydroxide are pumped into the mixing tank, the mixing pump speed is turned on at 1250r / min, and then input into the scraper tank, through the SMC unit, 25 parts of alkali-free glass fiber are added, and the impregnation is pressed by a pressure roller, and the equipment running speed is controlled to 10m / min to obtain a sheet;

[0069] Step 3: Roll and pack the sheet, send it to a drying room, control the temperature of the drying room at 42°C, and cure it for 11 hours to obtain a sheet molding compound.

[0070] Comparative Example 2: DOPO was not added, and the rest was the same as Example 4, specifically as follows:

[0071] Preparation of modified carbon nanotubes:

[0072] S1: Dissolve 12 parts of N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution, heat to 70°C, dropwise add the N-benzyl-N-(3-butene)amine solution into 10 parts of methyl dichlorophosphate solution, control the amount of methyl dichlorophosphate to be excessive so that the amino group in the N-benzyl-N-(3-butene)amine reacts with only one of the phosphorus-chlorine bonds, add 1 part of an acid-binding agent, triethylamine, react for 4 hours, filter, wash, and dry to obtain an intermediate A;

[0073] S2: Dissolve 10 parts of 2,4-diamino-6-phenyl-1,3,5-triazine and 8 parts of intermediate A in ethanol respectively, raise the temperature to 60°C, add intermediate A dropwise to 2,4-diamino-6-phenyl-1,3,5-triazine, control the excess of 2,4-diamino-6-phenyl-1,3,5-triazine, add 2 parts of acid-binding agent diisopropylethylamine, react for 8 hours, and obtain intermediate B;

[0074] S3: Dissolve 20 parts of intermediate B and 25 parts of acidified carbon nanotubes in ether, add 4 parts of 1,3-dicyclohexylcarbodiimide and 4 parts of 4-dimethylaminopyridine, stir for 40 minutes, heat to 80°C, react for 5 hours, and obtain modified carbon nanotubes.

[0075] Step 1: Add 60 parts of vinyl resin and 20 parts of polystyrene type low shrinkage agent into a stirring tank, stir at a speed of 1000r / min for 5min, then add 2.5 parts of zinc stearate, 28 parts of flame retardant (28 parts of modified carbon nanotubes), 1.5 parts of styrene, 0.5 parts of wetting agent, 1 part of PE powder, 0.4 parts of benzoquinone, 0.8 parts of tert-butyl perbenzoate, stir at a speed of 1200r / min for 8min to obtain a resin paste;

[0076] Step 2: The resin paste and 1 part of calcium hydroxide are pumped into the mixing tank, the mixing pump speed is turned on at 1250r / min, and then input into the scraper tank, through the SMC unit, 25 parts of alkali-free glass fiber are added, and the impregnation is pressed by a pressure roller, and the equipment running speed is controlled to 10m / min to obtain a sheet;

[0077] Step 3: Roll and pack the sheet, send it to a drying room, control the temperature of the drying room at 42°C, and cure it for 11 hours to obtain a sheet molding compound.

[0078] Comparative Example 3: A low-density sheet molding compound available on the market (purchased from Hua Ri Xin Cai) was used.

[0079] Testing experiment: The sheet-like film plastics of the above-mentioned embodiments and comparative examples were processed into corresponding shapes, and the limiting oxygen index was determined by using the national standard GB / T2406-2008 "Test method for combustion performance of plastics"; the density was determined by using the national standard GB / T1033.1-2008 "Determination of density of non-foamed plastics Part 1: Immersion method, liquid pycnometer method and titration method"; the impact strength was measured by using the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test". The obtained data are shown in the following table:

[0080] Test items Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Limiting oxygen index / % 32.7 25.9 26.1 29.4 <![CDATA[Impact strength (kJ / m 2 )]]> 14.9 12.8 13.1 13.8 density 1.41 1.76 1.69 1.45

[0081] Table 1

[0082] Conclusion: Compared with Comparative Example 3, Example 4 effectively enhances the flame retardant properties and strength of the obtained sheet-like film plastic by grafting and modifying carbon nanotubes and cooperating with DOPO. At the same time, carbon nanotubes can increase the porosity of the material and reduce the overall density of the material. Comparative Example 1 does not add modified carbon nanotubes, and the flame retardant properties and physical properties are reduced, and the density is also increased; Comparative Example 2 does not add DOPO, and the synergistic flame retardant effect is reduced, resulting in reduced flame retardant properties.

[0083] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A fiber-reinforced low-density high-flame-retardant sheet molding compound, characterized in that: The sheet molding compound comprises the following components: by weight, 55-75 parts of base resin, 12-25 parts of low shrinkage agent, 1-3 parts of release agent, 0.2-0.4 parts of polymerization inhibitor, 0.5-1 parts of thickener, 20-35 parts of flame retardant, 1-3 parts of crosslinking agent, 0.4-1 parts of initiator, 0.2-0.5 parts of impregnation agent, 0.5-1.5 parts of PE powder and 10-25 parts of reinforcing fiber.

2. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 1, characterized in that: The base resin includes one or more of unsaturated polyester and vinyl resin.

3. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 1, characterized in that: The low shrinkage agent includes one or more of a polystyrene-type low shrinkage agent and a saturated polyester low shrinkage agent; the release agent includes one or more of zinc stearate, magnesium stearate, and calcium stearate; the inhibitor includes one or more of hydroquinone, benzoquinone, trimethylbenzyl ammonium chloride and bromide; the thickener includes one or more of calcium oxide, magnesium oxide, calcium hydroxide, and magnesium hydroxide; the crosslinking agent is styrene; the initiator includes one or more of tert-butyl perbenzoate, benzoyl peroxide, tert-butyl peracetate, and tert-amyl perbenzoate; and the reinforcing fiber is alkali-free glass fiber.

4. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 1, characterized in that: The flame retardant includes one or more of melamine, DOPO and DMMP.

5. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 4, characterized in that: The flame retardant also includes modified carbon nanotubes.

6. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 5, characterized in that: The preparation process of the modified carbon nanotubes is as follows: S1: (1) dissolving N-benzyl-N-(3-butene)amine in dimethyl sulfoxide to obtain an N-benzyl-N-(3-butene)amine solution; (2) adding the N-benzyl-N-(3-butene)amine solution dropwise to methyl dichlorophosphate at 70-80° C., and adding triethylamine, reacting for 4-5 hours, filtering, washing, and drying to obtain intermediate A; S2: (1) dissolving 2,4-diamino-6-phenyl-1,3,5-triazine and intermediate A in ethanol respectively to obtain a 2,4-diamino-6-phenyl-1,3,5-triazine solution and an intermediate A solution; (2) adding the intermediate A solution dropwise to the 2,4-diamino-6-phenyl-1,3,5-triazine solution at 60-70° C., adding diisopropylethylamine, and reacting for 6-8 hours to obtain intermediate B; S3: Dissolve the intermediate B and the acidified carbon nanotubes in ether, add 1,3-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stir for 30-40 minutes, heat to 70-80° C., react for 4-5 hours, and obtain modified carbon nanotubes.

7. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 6, characterized in that: The intermediate A comprises the following components: by weight, 10-12 parts of methyl dichlorophosphate, 12-14 parts of N-benzyl-N-(3-butene)amine, and 1-2 parts of triethylamine; the intermediate B comprises the following components: by weight, 10-12 parts of 2,4-diamino-6-phenyl-1,3,5-triazine, 8-10 parts of intermediate A, and 1-2 parts of diisopropylethylamine; the modified carbon nanotubes comprise the following components: by weight, 15-20 parts of intermediate B, 20-25 parts of acidified carbon nanotubes, 2-4 parts of 1,3-dicyclohexylcarbodiimide, and 2-4 parts of 4-dimethylaminopyridine.

8. The fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 5, characterized in that: The flame retardant is a composition of modified carbon nanotubes and DOPO, and the weight ratio of the two is 1:(1-2.5).

9. The preparation method of a fiber-reinforced low-density high-flame-retardant sheet molding compound according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Add the base resin and low shrinkage agent into a stirring kettle, stir at a speed of 800-1000r / min for 2-5min, then add the release agent, polymerization inhibitor, crosslinking agent, wetting agent, PE powder, flame retardant, initiator, stir at a speed of 1000-1200r / min for 5-8min to obtain a resin paste; Step 2: The resin paste and thickener are pumped into the mixing tank, and then through the SMC unit, the reinforcing fiber is added, and the sheet is obtained by pressing and impregnating with a pressure roller; Step 3: Roll up and package the sheet, send it to a drying room for curing, and obtain a sheet molding compound.

10. The preparation method of a fiber-reinforced low-density high-flame-retardant sheet molding compound according to claim 9, characterized in that: The aging process parameters are: temperature 40-42° C., time 10-12 h.

Citation Information

Patent Citations

  • Low-density and high-flame-retardant SMC battery pack material and preparation method thereof and battery pack

    CN110591406A

  • Lightweight high-flame-retardant sheet-like molding compound and preparation method thereof

    CN111138820A

  • Degradable low-density flame-retardant epoxy SMC resin composition

    CN112029233A

  • Flame-retardant low-density sheet molding compound material and preparation method thereof

    CN113583418A